Uncovering labour trafficking: investigation tool for law enforcement and checklist for labour inspectors - Ylinen, Pekka (Publication series, 2020)
Identifying and investigating labour exploitation and trafficking is a challenging task. These are often international crimes in which migrant workers from one or more countries are brought to a third country, where their vulnerable position and ignorance are exploited by the offenders in multiple ways.